TRADISI LOKAL PAGANG GADAI DALAM MASYARAKAT MINAGKABAU - Hasneni - Hasneni (Islam Realitas: Journal of Islamic and Social Studies, 2015)
The implementation of ‘pagang gadai’ in Minangkabau’s local tradition is the lending agreement by giving assurance to the borrower, as long as the debt is not paid yet, so the assurance is still held by the borrower. This tradition arose through the principle of communal land ownership in Minangkabau’s maternal lineage that communal land ownership is not a private poverty and it cannot be traded. Thus, this local tradition came from an agreement that the main purpose was to help people inside the community. Moreover, it also has social function because most of people who pawn and lien holder is still in one community, in one tribe, and in one region. Besides, Islam came to Minangkabau when the tradition of “pagang gadai” had been a habitual tradition from generation to generation. However, in some views this tradition is contrary to Islamic rules; whether the pawning materials can be used by the pawning receiver. Pelaksanaan pagang gadai dalam tradisi lokal adat Minangkabau adalah perjanjian pinjam meminjam dengan memberikan jaminan kepada si peminjam, selama hutung itu belum dibayar maka barang jaminan akan tetap berada di tangan si peminjam. Tradisi ini muncul di tengah prinsip kepemilikan tanah yang bersifat komunal dalam adat matrineal Minangkabau bahwa tanah milik komunal adalah tanah yang tidak dimiliki secara privat dan tidak boleh diperjualbelikan. Sehingga tradisi lokal pagang gadai ini timbul dari suatu perjanjian yang bersifat tolong menolong, berfungsi sosial, sebab kebanyakan orang yang mengadaikan dan si pemegang gadai adalah orang yang masih sekaum, sesuku, dan sejauh-jauhnya adalah senagari. Di samping itu, Islam masuk ke dalam masyarakat adat Minangkabau disaat tradisi pagang gadai telah menjadi kebiasaan turun temurun masyarakatnya. Namun dalam beberapa pandangan, tradisi pagang gadai ini terdapat pertentangan dengan apa yang diatur oleh hukum Islam. Pertentangan terjadi dalam hak apakah barang gadaian itu boleh dimanfaatkan oleh si penerima gadai.